2022
DOI: 10.1039/d2cc03722j
|View full text |Cite
|
Sign up to set email alerts
|

In situ preparation of glyco-micromotors and their bacteria loading/guiding ability

Abstract: We successfully synthesized glyco-micromotors in situ directed by multifunctional glycopolymers. The fabricated glyco-micormotor presents abilities in loading and guiding bacteria with different individual and group motions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
(50 reference statements)
0
3
0
1
Order By: Relevance
“…目前多糖或糖聚合物修饰的光响应型微马达主要 通过调控紫外光光源 [31][32] 或依靠催化分解过氧化氢 [33] 来实现自驱动, 然而这两种能量来源对生物体有一定的 损害. 基于此, 本工作希望开发一种以可见光和纯水为 能量来源的甘露糖修饰的微马达.…”
Section: 引言unclassified
“…目前多糖或糖聚合物修饰的光响应型微马达主要 通过调控紫外光光源 [31][32] 或依靠催化分解过氧化氢 [33] 来实现自驱动, 然而这两种能量来源对生物体有一定的 损害. 基于此, 本工作希望开发一种以可见光和纯水为 能量来源的甘露糖修饰的微马达.…”
Section: 引言unclassified
“…The built-in carbohydrate functional groups of the micromotors facilitate its interaction with sugar groups in the membrane of E. coli bacteria. [17] While promising, the previously developed micromotors based strategies focused only on bacteria isolation or lacked selectivity due to the use of non-specific probes such as lectins or carbohydrates. Another interesting approach described by Wang et al [18] reported on the use of biocompatible high-motility Janus particles that can accumulate passive beads at the surface in the form of clusters and then release them in a controlled manner (under the action of light) at the intended location.…”
Section: Introductionmentioning
confidence: 99%
“…The built‐in carbohydrate functional groups of the micromotors facilitate its interaction with sugar groups in the membrane of E. coli bacteria. [ 17 ] While promising, the previously developed micromotors based strategies focused only on bacteria isolation or lacked selectivity due to the use of non‐specific probes such as lectins or carbohydrates. Another interesting approach described by Wang et al.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10] This is largely due to a significant range of applied problems that can be solved with their help. 11,12 Because of their mobility, micromotors demonstrate amazing properties of self-organization during collective movement. 13,14 The range of mechanisms responsible for the micromotor movement is extremely diverse and is associated with the occurrence of chemical reactions in the system, the action of interfacial forces, thermophoresis, magnetic, electrical, acoustic fields, and even quantum effects.…”
mentioning
confidence: 99%